Taxonomic notes on some species and subspecies of aphids (Hemiptera: Aphididae) - Stekolshchikov, Andrey V. (Zootaxa, 2014)
Subspecies Dysaphis pavlovskiana indica Chakrabarti & Medda, 1993 is given species status (Dysaphis indica Chakrabarti & Medda, 1993, new status). Aphis plantaginis asiatica Daniyarova, 1979 is a synonym of Aphis taraxacicola (Börner, 1940). The nomen nudum Uroleucon (Uromelan) lehri Zaitzev, Lelej, Storozhenko & Kurzenko, 2006 is recognized as referring to Uroleucon (Uromelan) campanulae (Kaltenbach, 1843).